A 17 ka multi‐proxy paleoclimatic record on the northeastern Tibetan Plateau: implications for the northernmost boundary of the Asian summer monsoon during the Holocene. (29th June 2021) - Wang, Haipeng; Hu, Yu; Zhang, Xu; Lv, Feiya; Ma, Xueyang; Wu, Duo; Chen, Fahu; Zhou, Aifeng; Hou, Juzhi; Chen, Jianhui
Abstract: Knowledge of the paleoclimatic record of the northeastern Tibetan Plateau (NETP) can potentially improve our understanding of the evolution of the Asian summer monsoon (ASM). However, the history of climate change and inferred spatial extent of the ASM on the NETP since the last deglaciation remain unclear. Here, we use several environmental proxies from the sediments of Hala Lake (beyond the modern limit of ASM), including chironomids, loss‐on‐ignition, grain size and element data, to explore the climatic history of the NETP and the northern boundary of the ASM since the last deglaciation. The results document a series of climatic events during the deglaciation, including Heinrich Event 1, the Bølling–Allerød interstadial and the Younger Dryas event. The records also reveal the timing of the megathermal and precipitation maximum, the lake‐level maximum, and strongest chemical weathering, which occurred during 10–7 ka. The inferred precipitation maximum during the early Holocene in the Hala Lake basin, which can be verified by the simulated precipitation change, is consistent with that in typical Indian summer monsoon (ISM) regions, suggesting that the ISM has penetrated into Hala Lake basin at that time. The monsoon‐dominated climate in the Hala Lake basin during the early Holocene and the westerlies‐dominated climate in the arid central Asia indicate that the maximum areal extent of the ASM on the NETP since the last deglaciation lay to the northwest of Hala Lake basin. In combination with other published records, the northernmost boundary of the ASM over China since the last deglaciation has been tentatively delineated, to shed some lights on this long‐standing debate. Abstract : The northern boundary of the Asian summer monsoon (ASM) during the Holocene suggested by the previous study is contrary to the Holocene moisture evolution in the arid of northwest China dominated today by the Westerlies. Multi‐proxy analyses from Hala Lake, located beyond the modern ASM boundary, indicated that the ASM has penetrated into Hala Lake basin during the early Holocene. In combination with the published records from the Alxa Plateau and the northern, central and western Tibetan Plateau, the northernmost boundary of the ASM over China since the last deglaciation has been tentatively delineated.